Frequency of Pseudophakic Glaucoma in a Tertiary Care Hospital of Pakistan - Shahid Anwar Bhatti, Mohammad Parvez, Faisal Nawaz, Muhammad Waseem, Abdul Munim, Naseer Ahmad, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Glaucoma after cataract surgery with intraocular lens inserting is known as pseudophakic glaucoma and its prevalence varies greatly around the world. Objective: The aim of this study was to find out the Pseudophakic Glaucoma Frequency in a Tertiary Care Hospital. Methodology: The current study was conducted at the department of ophthalmology Ophthalmology Muhammad college of Medicine Peshawar from April 2022 to November 2022 after taking permission from the ethical board of the hospital. A total of 216 Pseudophakic individuals’ with age range of 50–70 who had intraocular lens implantations in the anterior and posterior chambers within a minimum of 6 weeks and a maximum of 5 years after surgery were included in this study. An eye examination was performed. Snellen's chart was used to measure visual acuity. Intraocular pressure (IOP) was measured using applanation tonometry. Angle was measured with gonioscopy's assistance. A thorough fundoscopic examination of the RNFL and disc was conducted. To diagnose glaucoma perimetry and optical coherence tomography was done. When a patient had previously undergone cataract surgery, pseudophakic glaucoma was diagnosed. SPSS version 20 was used for data analysis. Results: Over all 216 individuals took part in this research. 30 individuals (13.8%) of them were found to have pseudophakic glaucoma. Ten (33.33%) people had phacoemulsification, and twenty (66.0%) had extracapsular cataract extraction. Eight patients (23.33%) had anterior chamber intraocular lenses, while 22 patients (73.33%) had posterior chamber intraocular lenses. After cataract surgery, the average presentation time was 2.7 ± 2.6 years. Posterior capsular rupture was the most common cause of pseudophakic glaucoma 17 (56.66%) followed by UGH 3 (10.%) & pupillary block 5 (16.66%) . Retained lens matter 1 (3.33%) and YAG, or laser capsulotomy 2 (6.66.1%) were less frequent. The primary cause for pseudophakic glaucoma at the time of surgery was a posterior capsular rupture. Conclusion: The current study came to the conclusion that anterior chamber intraocular lenses have a stronger connection to pseudophakic glaucoma than sulcus-implanted posterior chamber lenses. Keywords: Anterior chamber; Pseudophakic glaucoma; Posterior chamber